Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/meg.0000000000001132
|View full text |Cite
|
Sign up to set email alerts
|

Short article: Safety of targeted prophylaxis strategy in patients with resolved hepatitis B virus infection receiving rituximab for immune-mediated diseases

Abstract: The results supported the low to moderate risk of HBVr in HBsAg-negative/HBcAb-positive patients with IMID undergoing RTX, in contrast to what is observed in onco-hematological settings. The targeted prophylaxis strategy, based on serum HBV-DNA serial monitoring, seems a safe option in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A total of 32 studies were identified evaluating immunosuppressing biologics and other disease-modifying antirheumatic drugs (DMARDs) for autoimmune diseases, which included rheumatoid arthritis, psoriasis, systemic lupus erythematosus, and aplastic anemia (Table 4). 67-98 TNFα inhibitors were the most common agents evaluated, and 6 studies included rituximab. Use of prophylaxis was rare.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 32 studies were identified evaluating immunosuppressing biologics and other disease-modifying antirheumatic drugs (DMARDs) for autoimmune diseases, which included rheumatoid arthritis, psoriasis, systemic lupus erythematosus, and aplastic anemia (Table 4). 67-98 TNFα inhibitors were the most common agents evaluated, and 6 studies included rituximab. Use of prophylaxis was rare.…”
Section: Resultsmentioning
confidence: 99%
“…A typical cycle consists of 1000 mg for 2 doses spaced 2 weeks apart, with cycles able to be repeated after 6 months. Although only 6 studies using rituximab for immune disease were identified, 68,76,82,86,88,91 the approximate 6% HBVr rate for rituximab was more than twice that of the 2.4% rate observed for other biologic agents, and reactivation was observed even after just 1 cycle. 91 Additionally, among the patients receiving biologic agents for autoimmune disease, all 4 noted cases of hepatitis flare were observed with rituximab, whereas no cases were observed among patients receiving other biologic agents.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
“…On the other hand, 4 subsequent studies reported a total of 7 cases of reactivation over 119 patients, with a reactivation rate ranging from 3 to 9.1% [18][19][20][21]. Interestingly, 4 of these 7 patients were from Taiwanese cohort, whereas 3/7 subjects came from three different cohorts of European patients [18][19][20] and 2 of them were affected with cryoglobulinemia [20,21]. Of note, cryoglobulinemia is a multifaceted condition that may be considered an immune-hematological disease rather than purely rheumatic.…”
Section: Discussionmentioning
confidence: 99%